2022
DOI: 10.3389/fpubh.2022.881069
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Late Antiretroviral Therapy Initiation Among People Living With HIV in Southern Iran: A Historical Cohort Study

Abstract: ObjectivesLate initiation of antiretroviral therapy (ART) is associated with poor outcome among people living with HIV (PLHIV) and higher risk of transmission of infection. This study was conducted to identify the determinants of late ART initiation among PLHIV in Southern Iran.MethodsA historical cohort study was conducted on 1,326 PLHIV of ≥15 years of age who were registered with the behavioral diseases counseling center (BDCC) in southern Iran from August 1997 to March 2021. Late ART initiation was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
4
5
2
Order By: Relevance
“…The study also demonstrated that males were associated with delayed ART-initiation. This finding, however, differs with studies from Canada (Joseph, et al, 2016) and the US [105] where no association between gender and time-to-ART-initiation was observed and from southern Iran study which reported no association between gender and treatment initiation times [103]. However, studies from Zimbabwe [106], Ethiopia [107], and Cameroon [108], reported that male gender was a risk factor for late-ART-presentation – therefore, a barrier to rapid treatment-initiation.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The study also demonstrated that males were associated with delayed ART-initiation. This finding, however, differs with studies from Canada (Joseph, et al, 2016) and the US [105] where no association between gender and time-to-ART-initiation was observed and from southern Iran study which reported no association between gender and treatment initiation times [103]. However, studies from Zimbabwe [106], Ethiopia [107], and Cameroon [108], reported that male gender was a risk factor for late-ART-presentation – therefore, a barrier to rapid treatment-initiation.…”
Section: Discussioncontrasting
confidence: 84%
“…(aOR: 1.8, 95%CI:1.17-2.78) [103] as was also reported in China [104]. This study also found that dependency on guardian escort was 9% negatively associated with early ARTinitiation.…”
Section: A D J U S T E D H a Z A R D R A T I O F O R T T A T -I N I T...supporting
confidence: 84%
See 1 more Smart Citation
“…We found that patients who diagnosed after 2016 had a shorter duration to initiate ART compared to those diagnosed before 2016. In accordance with this finding, a study from southern Iran on 1,326 adult HIV patients showed that initiating ART during 2011–2013 had 3.65 odds [95% CI 2.28, 5.86] for late ART initiation compared to more recent years (2018–2021) 38 . Additionally, Lahuerta et al 28 and Ndawinz et al 39 found that patients initiating ART in recent calendar years had lower odds of late ART initiation Moreover, a study from China showed a constant decline in delayed ART initiation from 2010 to 2020, with a sharp decrease in 2016 (58.0% to 36.9%), coinciding with national guideline reforms 40 .…”
Section: Discussionsupporting
confidence: 61%
“…A study on 1180 Ethiopian adults found that being male was associated with higher odds of late ART initiation (aOR: 2.02 [95% CI 1.50, 2.73]) 42 . Another study in Iran also observed similar findings (OR: 0.41 [95% CI 0.31, 0.55]) 38 . The lower likelihood of late ART initiation in females could be justified by routine testing and care during antenatal visits provided by Prevention of Mother to Child Transmissions (PMTCT) services 43 45 , and differences in health-seeking behavior 46 .…”
Section: Discussionsupporting
confidence: 61%